Modelling of stiffness degradation due to cracking in laminates subjected to multi-axial loading - Kashtalyan, M. (Philos Trans A Math Phys Eng Sci, 2016)
The paper presents an analytical approach to predicting the effect of intra- and interlaminar cracking on residual stiffness properties of the laminate, which can be used in the post-initial failure analysis, taking full account of damage mode interaction. The approach is based on a two-dimensional shear lag stress analysis and the equivalent constraint model of the laminate with multiple damaged plies. The application of the approach to predicting degraded stiffness properties of multidirectional laminates under multi-axial loading is demonstrated on cross-ply glass/epoxy and carbon/epoxy laminates with transverse and longitudinal matrix cracks and crack-induced transverse and longitudinal delaminations. This article is part of the themed issue ‘Multiscale modelling of the structural integrity of composite materials’.